2014
DOI: 10.1038/ncomms4936
|View full text |Cite
|
Sign up to set email alerts
|

Separating NADH and NADPH fluorescence in live cells and tissues using FLIM

Abstract: NAD is a key determinant of cellular energy metabolism. In contrast, its phosphorylated form, NADP, plays a central role in biosynthetic pathways and antioxidant defence. The reduced forms of both pyridine nucleotides are fluorescent in living cells but they cannot be distinguished, as they are spectrally identical. Here, using genetic and pharmacological approaches to perturb NAD(P)H metabolism, we find that fluorescence lifetime imaging (FLIM) differentiates quantitatively between the two cofactors. Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
459
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(484 citation statements)
references
References 57 publications
21
459
2
2
Order By: Relevance
“…In addition, initial superoxide signals produced by the NADPH oxidase can stimulate secondary mitochondrial superoxide and various ROS production. It could be also that proton channels play a role in UPE generation, as the NADPH-NADP + balance (Blacker et al, 2014) has a key role in redox and ROS-mediated processes that are the bases for photon emission processes. Kobayashi et al (1999b) reported an increase in UPE induced by the addition of 10 mm glutamate.…”
Section: Phosphene Generation In the Visual Cortex By Means Of Excessmentioning
confidence: 99%
“…In addition, initial superoxide signals produced by the NADPH oxidase can stimulate secondary mitochondrial superoxide and various ROS production. It could be also that proton channels play a role in UPE generation, as the NADPH-NADP + balance (Blacker et al, 2014) has a key role in redox and ROS-mediated processes that are the bases for photon emission processes. Kobayashi et al (1999b) reported an increase in UPE induced by the addition of 10 mm glutamate.…”
Section: Phosphene Generation In the Visual Cortex By Means Of Excessmentioning
confidence: 99%
“…The fluorescence lifetime, or the amount of time a fluorophore remains excited prior to decaying back to the ground state, provides complementary information to the redox ratio [16,19]. The fluorescence lifetime is sensitive to changes in cell microenvironment, such as pH, protein binding, and proximity to fluorescence quenchers such as oxygen [20][21][22]. Fluorescence lifetime imaging microscopy (FLIM) is an optical imaging technique capable of resolving these changes on a single-cell basis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal partitioning of glycolytic and oxidative metabolism can be resolved by measuring cytoplasmic and mitochondrial NAD(P)H changes (Patterson et al, 2000). The different roles of NADH and NAD(P)H in ATP production and antioxidant defense can be separated by simultaneously measuring two-photon NAD(P)H and one-photon lipoamide dehydrogenase autofluorescence (Rocheleau et al, 2004) or by fluorescence lifetime imaging (Blacker et al, 2014). The dynamics of lipid partitioning and fatty acid oxidation can be modeled by monitoring electron transfer flavoprotein autofluorescence (Lam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%